EVALUATION OF RENNELLIA ELLIPTICA AS POTENTIAL ANTIPLASMODIAL HERBAL REMEDY (Jurnal Teknologi (Sciences & Engineering), 2017)
Rennellia elliptica (Rubiaceae) has been used by local Jakun Community in the Endau Rompin State Park for the treatment of jaundice. Previous study has revealed the antiplasmodial activity of the root extract and major anthraquinones isolated from the roots. The present study entails the optimization of extraction methods, qualitative and quantitative analyses of selected marker anthraquinones and in vivo antiplasmodial activity along with toxicity and inhibition of Î²-hematin in vitro. HPLC profile showed the present of marker compounds as major constituents with content ranging 3-12 Âµg/g extract. The root extract showed potent antiplasmodial activity against rodent malaria, Plasmodium berghei with ED50 value of 1.23 Âµg/ml BW. The major anthraquinones, damnacanthal and nordamnacanthal showed significant inhibition against Î²-hematin formation via lipids and HRP2 catalyses. However, the root extract is slightly toxic against hepatocyte cell. These data suggests that R. elliptica is a potential herbal remedy for malaria treatment and antiplasmodial of the root extract possibly due to the action of major anthraquinones.Â